Supporting mental health and psychosocial wellbeing through social and emotional learning: A participatory study of conflict-affected youth resettled to the U.S. - Lindsay Stark; Mackenzie V. Robinson; Alli Gillespie; Jeremy Aldrich; Wafa Hassan; Michael Wessells; Carine Allaf; Cyril Bennouna (BMC Public Health, 2021)
Abstract Background A growing literature has drawn attention to the central role that schools play in supporting the adjustment of resettled refugee youth and promoting their mental health and psychosocial wellbeing. In particular, the recent proliferation of school-based social and emotional learning (SEL) initiatives presents an opportunity to strengthen supports for resettled adolescents. This participatory research study aims to understand how high school students resettled from countries in the Middle East and North Africa region are experiencing the challenges and opportunities of acculturation and the ways in which they believe schools can better support them in this process. Methods We analyzed primary data collected during focus group discussions as part of the SALaMA study. During these discussions, we used participatory ranking methodology to elicit adolescents’ suggestions on how high schools can better support students both academically and psychosocially after resettlement. Fourteen focus group discussions were held with male (n = 38) and female (n = 31) adolescents aged 14–20 years, who were selected purposively across six public high schools in Harrisonburg, Virginia, Austin, Texas, and Detroit, Michigan. Participants offered suggestions and then ranked them in order of importance using consensus ranking. Results Thematic analysis of the PRM results across sites produced a wealth of suggestions centered around three broad themes, namely: skills related to navigating social and academic challenges, culturally responsive teaching, and socially and culturally equitable learning environments. Conclusions Findings reported illustrate limitations of the conventional, universal SEL model and shed light on how schools can adapt transformative SEL strategies to serve their students better, especially newcomers from conflict-affected countries.